Assessment of Phasic Changes of Vascular Size by Automated Edge Tracking-State of the Art and Clinical Perspectives - Mesin, Luca; Albani, Stefano; Policastro, Piero; Pasquero, Paolo; Porta, Massimo; Melchiorri, Chiara; Leonardi, Gianluca; Albera, Carlo; Scacciatella, Paolo; Pellicori, Pierpaolo; Stolfo, Davide; Grillo, Andrea; et al. (Frontiers in Cardiovascular Medicine, 2022)
Assessment of vascular size and of its phasic changes by ultrasound is important for the management of many clinical conditions. For example, a dilated and stiff inferior vena cava reflects increased intravascular volume and identifies patients with heart failure at greater risk of an early death. However, lack of standardization and sub-optimal intra- and inter- operator reproducibility limit the use of these techniques. To overcome these limitations, we developed two image-processing algorithms that quantify phasic vascular deformation by tracking wall movements, either in long or in short axis. Prospective studies will verify the clinical applicability and utility of these methods in different settings, vessels and medical conditions.